51.4k views
22 votes
What is a correct first step in solving the inequality –4(3 – 5x)≥ –6x + 9?

–12 – 20x ≤ –6x + 9
–12 – 20x ≥ –6x + 9
–12 + 20x ≤ –6x + 9
–12 + 20x ≥ –6x + 9

User Nita
by
5.0k points

1 Answer

2 votes

Answer:

-12 + 20x ≥ -6x + 9

Fourth choice

Explanation:

Inequalities

We are given the inequality:

-4(3 - 5x) ≥ -6x + 9

Solving the inequality implies having x isolated on one of the sides.

We must start by removing the parentheses. It will be done by multiplying -4 by (3 - 5x). Since this operation doesn't imply multiplying all the inequality by a negative number, the sign won't be flipped:

-4*3 - (-4)5x ≥ -6x + 9

Multiplying:

-12 + 20x ≥ -6x + 9

Fourth choice

User CKII
by
4.9k points